Aratati ca:(×-3)(×+3)(×^2+9)(×^4+81)(×^8+3^8)=×^16-3^16
albatran:
ia din aproape in aproape!
Răspunsuri la întrebare
Răspuns de
2
(×-3)(×+3)(×^2+9)(×^4+81)(×^8+3^8)=×^16-3^16
(×^2-9)(×^2+9)(×^4+81)(×^8+3^8)=
=(×^4-81)(×^4+81)(×^8+3^8)=
=(×^4-3^4)(×^4+3^4)(×^8+3^8)=
=(×^8-3^8)(×^8+3^8)=
=x^16-3^16
formula aplicata (a-b)(a+b)=a^2-b^2
(×^2-9)(×^2+9)(×^4+81)(×^8+3^8)=
=(×^4-81)(×^4+81)(×^8+3^8)=
=(×^4-3^4)(×^4+3^4)(×^8+3^8)=
=(×^8-3^8)(×^8+3^8)=
=x^16-3^16
formula aplicata (a-b)(a+b)=a^2-b^2
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă